Development Of An Information Technology-Based English Curriculum Today - Weni Wulandari; Sabarun Sabarun; Zaitun Qamariah (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to develop an information technology-based English curriculum in response to the increasing demand for language learning in the digital era. This study uses a qualitative research method, which involves acknowledging the literature and opinions of experts in the fields of language teaching and technology integration. The findings of this study reveal that the development of an information technology-based English curriculum can improve students' language learning outcomes by providing interesting and interactive learning materials and activities. In addition, this study also found that the incorporation of technology in language teaching can increase learner autonomy, collaborative learning, and authentic use of language.